2017
DOI: 10.1002/jbm.a.35975
|View full text |Cite
|
Sign up to set email alerts
|

When size matters: differences in demineralized bone matrix particles affect collagen structure, mesenchymal stem cell behavior, and osteogenic potential

Abstract: Demineralized bone matrix (DBM) is a natural, collagen-based, osteoinductive biomaterial. Nevertheless, there are conflicting reports on the efficacy of this product. The purpose of this study was to evaluate whether DBM collagen structure is affected by particle size and can influence DBM cytocompatibility and osteoinductivity. Sheep cortical bone was ground and particles were divided in three fractions with different sizes, defined as large (L, 1-2 mm), medium (M, 0.5-1 mm), and small (S, <0.5 mm). After dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…Despite a considerable number of reports employing ovine MSCs (oMSCs) in tissue engineering (Al Faqeh, Nor Hamdan, Chen, Aminuddin, & Ruszymah, ; Boos et al, ; Di Bella et al, ; Dozza et al, ; Lucarelli et al, ; Mrugala et al, ; Scharf et al, ), thereare limited studiesregarding their morphological and biochemical characterization (Burk et al, ; Desantis et al, ; Lyahyai et al, , McCarty, Gronthos, Zannettino, Foster, & Xian, ; Mrozik et al, ; Rentsch et al, ; Zannettino, Paton, Itescu, & Gronthos, ). Differently from human MSCs, oMSCs are not well studied for their physiological activity and behaviour in tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a considerable number of reports employing ovine MSCs (oMSCs) in tissue engineering (Al Faqeh, Nor Hamdan, Chen, Aminuddin, & Ruszymah, ; Boos et al, ; Di Bella et al, ; Dozza et al, ; Lucarelli et al, ; Mrugala et al, ; Scharf et al, ), thereare limited studiesregarding their morphological and biochemical characterization (Burk et al, ; Desantis et al, ; Lyahyai et al, , McCarty, Gronthos, Zannettino, Foster, & Xian, ; Mrozik et al, ; Rentsch et al, ; Zannettino, Paton, Itescu, & Gronthos, ). Differently from human MSCs, oMSCs are not well studied for their physiological activity and behaviour in tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…Though no specific, isolated biological agents inducing osteogenic differentiation, such as plasmid DNA, PDGF, or BMP‐2, were added in this study, DBM has been shown to retain some BMP proteins and collagens (Wildemann, Kadow‐Romacker, Haas, & Schmidmaier, ). For prior studies in the rat model with DBM inclusion (Ding et al, ; Dozza et al, ), correlations between osteogenic gene expression and ALP/calcium deposition have shown, specifically that DBM was associated with osteogenic gene expression, including COL1A1, ALP, OCN, and ONN. The effect of adding Mg to the polymer/DBM scaffold is consistent with earlier reports with Mg‐containing materials (Liu et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…This bone‐derived product provides an array of biologically active molecules, including BMP‐2 and a variety of other growth factors at more physiologic concentrations (Wildemann et al, ), as well as collagens and other ECM components to promote osteoconduction and osteoinduction (Khoshzaban et al, ). Although DBM has been shown to be effective in some preclinical bone healing scenarios (Alidadi, Oryan, Bigham‐Sadegh, & Moshiri, ; Dozza et al, ), there is less evidence of efficacy in clinical trials (Kinney, Ziran, Hirshorn, Schlatterer, & Ganey, ), and in several preclinical studies, the osteogenic efficacy of DBM alone may not be enough (Rhee et al, ; Van Houdt et al, ). Further, the material presents some challenges associated with handling, stability after surgery, and identification of an appropriate carrier (Maddox, Zhan, Mundy, Drohan, & Burgess, ).…”
Section: Discussionmentioning
confidence: 99%
“…All the scaffolds were sterilized by 30 min of incubation in absolute EtOH followed by three washes in DPBS (30 min each one). Then cubic-shaped sections of about 1 mm on each side were produced using scalpel blades 30 sections were inserted into a microtube containing 500 µL of PGM culture medium and incubated over night at 4 • C. The day after, VW-MSCs were seeded on different biomaterials (PLA-10CaSi-10DCPD and PCL-10CaSi-10DCPD) following a published method [34] with some main adaptations. Microtubes with the biomaterials were incubated to reach a temperature of 38 • C. The medium was then separated, and biomaterials were drop-seeded with 100 µL of a concentrated cell suspension containing 4 × 10 5 or 8 × 10 5 cells.…”
Section: Cell Seeding Efficiency Assaymentioning
confidence: 99%
“…Cell seeding efficiency (CSE) was estimated using an indirect method [34] after 24, 48 and 72 h. Briefly, CSE was calculated using the following equation: CSE (%) = (1 − cells u /cells i ) × 100, where cells i is the number of cells initially seeded and cells u is the number of unattached cells in the residual medium and in DPBS used for rinsing cell-seeded biomaterials. Unattached cells were counted by hemocytometer in three different aliquots of medium collected from each sample.…”
Section: Cell Seeding Efficiency Assaymentioning
confidence: 99%